1999
DOI: 10.1093/ejo/21.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Changes in airway and hyoid position in response to mandibular protrusion in subjects with obstructive sleep apnoea (OSA)

Abstract: This prospective clinical study examined the alterations in airway and hyoid position in response to mandibular advancement in subjects with mild and moderate obstructive sleep apnoea (OSA). Pairs of supine lateral skull radiographs were obtained for 13 female and 45 male, dentate Caucasians. In the first film, the teeth were in maximal intercuspation, while in the second the mandible was postured forwards into a position of maximum comfortable protrusion. Radiographs were traced and digitized, and the alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
87
0
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 39 publications
15
87
0
19
Order By: Relevance
“…Our result agrees with those of previous studies [29,30] that also reported that a wider lower pharyngeal airway resultant from anterior positioning of the mandible in his their subjects.…”
Section: Lowersupporting
confidence: 94%
See 3 more Smart Citations
“…Our result agrees with those of previous studies [29,30] that also reported that a wider lower pharyngeal airway resultant from anterior positioning of the mandible in his their subjects.…”
Section: Lowersupporting
confidence: 94%
“…Yamaoka et al [28] found that the tongue root was situated more posteriorly in Class II females subjects compared with Class III ones. Also, the change in hyoid bone position and lower pharyngeal airway space caused by anteroposterior position of the mandible is well documented [29].In our study the depth of the inferior pharyngeal airway was increased, and had a significant correlation with the changes in SNB angle, ANB angle, and the distance from Pog to N perp. These results suggest that as the mandible was anteriorly positioned in our subjects, the tongue root was positioned more anteriorly away from the posterior pharyngeal wall, the hyoid bone as well was positioned more anteriorly, and as a consequence, the lower pharyngeal airway was widened.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Os outros 7 pacientes não deram continuidade ao tratamento, pois alegaram desconforto durante a utilização. O índice de aceitação pode ser considerado baixo, quando comparado ao do estudo clínico de Battagel et al 3 , que verificou um índice de cooperação de 76%. O desconforto alegado pelos pacientes ao utilizarem o aparelho refere-se a dificuldades de adaptação devidas aos efeitos colaterais produzidos pelo uso do Bionator de Balters.…”
Section: Discussionunclassified